Biological Parts for Kluyveromyces marxianus Synthetic Biology - Rajkumar, Arun S.; Varela, Javier A.; Juergens, Hannes; Daran, Jean-Marc G.; Morrissey, John P. (Frontiers in Bioengineering and Biotechnology, 2019)
Kluyveromyces marxianus is a non-conventional yeast whose physiology and metabolism lends itself to diverse biotechnological applications. While the wild-type yeast is already in use for producing fragrances and fermented products, the lack of standardised tools for its genetic and metabolic engineering prevent it from being used as a next-generation cell factory for bio-based chemicals. In this paper, we bring together and characterise a set of native K. marxianus parts for the expression of multiple genes for metabolic engineering and synthetic biology. All parts are cloned and stored according to the MoClo/Yeast Tool Kit standard for quick sharing and rapid construction. Using available genomic and transcriptomic data, we have selected promoters and terminators to fine-tune constitutive and inducible gene expression. The collection includes a number of known centromeres and autonomously replication sequences (ARS). We also provide a number of chromosomal integration sites selected for efficiency or visible phenotypes for rapid screening. Finally, we provide a single-plasmid CRISPR/Cas9 platform for genome engineering and facilitated gene targeting, and rationally create auxotrophic strains to expand the common range of selection markers available to K. marxianus. The curated and characterised tools we have provided in this kit will serve as a base to efficiently build next-generation cell factories from this alternative yeast. Plasmids containing all parts are available at Addgene for public distribution.